ВОЛЮНТАРИЗМ ЯК ТЕЧІЯ ІРРАЦІОНАЛІЗМУ У ФІЛОСОФІЇ ПРАВА - Музика, Марія Петрівна (SUPREMANCE OF LAW, 2018)
This article investigates voluntarism as a type of irrationalism in law. Common and different features were analyzed in the philosophical and legal concepts of the will in the works of A. Schopenhauer and F. Nietzsche. The philosophers both treat the phenomenon of the will as: comprehending mind only as ability to highlight the subjectivity of human personality; understanding the will as a supraindividual phenomenon, characterized by substantive basis of legal existence; law must influence the will, but not the intellect of a person; the will is primary in relation to consciousness and thinking; the will is an integral part of human activity; a person is an irrational creature who lives by instincts, unconscious motivations. A. Schopenhauer and F. Nietzsche interpret the phenomenon of the will in the philosophy differently in the following aspects: F. Nietzsche believes that the will is a definite individual will of a person which is showed as “will to authority”, or rather “will to power”, but A. Schopenhauer thinks that the will is endless in its manifestations, it can be both world and individual; according to F Nietzsche the principle “will to authority” creates inequality of people, which is the essence of social life, eternal dominance over others; according to A. Schopenhauer, the will must be embodied in justice, which means observance of the limits of the establishment of his will and recognition of self-restraint of the personality’s behavior; in the philosophy of law of A. Schopenhauer the will is characterized by pessimistic and ascetic motives, but in the concept of “will to power” F Nietzsche clearly traces the aspects of activism and optimism. It was proposed to treat voluntarism as a kind of irrationalism in law as philosophical and legal branch, in which the will is recognized as the fi rst principle of legal existence and cognition, and is important in self-regulation by a person of his behavior and activities. It was found out that voluntarism as a kind of irrationalism in law, the following features are inherent in the will: it challenges the meaning of the mind as a sphere of recognition of human activity; is the root cause of all social and legal processes; determines the course of psychological and mental processes in humans; is a motivation force of intellect and has advantages over legal rationalism; it is understood as the phenomenon of self-regulation by a subject of the right of his activity; it is defi ned as motives, motivation for action; determines the orientation of legal knowledge; forms a legal being; acts as an absolute beginning to legal life. It has been established that voluntarism as a form of irrationalism in law is divided into two subtypes, depending on the philosophy of law of two main representatives: A. Schopenhauer and F Nietzsche.